Research of oxidative stability of vegetable oils for use in sport nutrition - Sytnik, Natalia; Mazaeva, Viktoria; Bilous, Olesia; Bukhkalo, Svitlana; Glukhykh, Valentyna; Sabadosh, Ganna; Natarov, Vadym; Yarmysh, Natalia; Kravchenko, Tetiana; Zakharkiv, Stepan (Technology audit and production reserves, 2019)
The object of research is sunflower, high oleic sunflower and rapeseed oils, which are important in the production of food for people with increased physical activity. Such products should be balanced in component composition and enriched with biologically active substances, vitamins, antioxidants. Oils and fats are used as an important component of sport nutrition. Common oil is sunflower oil, which provides the diet with linoleic acid, as well as rapeseed oil, which enriches the products with linolenic acid. One of the most problematic places to use oils is oxidative damage, as this leads to the formation of hazardous compounds. During the study, the active oxygen method and the Oxitest device (Italy) were used. The first method allows to directly assess the content of oxidation products in the oil through the values of the peroxide value, the second method allows to measure oxygen consumption during oxidation processes in the oil. The oxidative stability of sunflower oil is studied using the active oxygen method and the oxidation method using the Oxitest device at a temperature of 110 °C. It is found that the induction periods determined by the two methods are close (2 hours 40 minutes and 2 hours 43 minutes, respectively). The regularity of reducing the induction period of sunflower oil with increasing temperature by the oxidation method on an Oxitest device is established. The temperatures of 90, 100 and 110 °C are used. A comparative study of the oxidative stability of sunflower, high oleic sunflower and rapeseed oils is carried out. Based on the obtained data, a comparative characteristic of the stability of research oils to oxidation is given and recommendations for their use in sports nutrition are given. The obtained data will allow to evaluate the effect of each of the experimental oils on the shelf life of the oil-containing product.